Characteristics Study of Wireless Power Transfer with SeriesSeries Inductive Magnetic Coupled Principle - Baswara, Ahmad Raditya Cahya (Signal and Image Processing Letters, 2019)
The wireless power transfer system using series-series inductive coupled magnetic resonance is studied in this work. The research is conducted using two separated circular coil facing each other serving as transmitter and reciver coil respectively. The effect of distance variation between two coils as well as loading variation to power efficiency and other electrical properties such as current, voltage, active power, and efficiency are observed. The coil's number of turn, transmitter input voltage, coil's attitude, and electrical frequency of the system are kept constant. The results show that the inter-coil distance value affect the overall performance of wireless power transfer system and match the theoretical prediction.